Comparison of Antioxidant Activity and Main Active Compounds Among Different Parts of Alpinia officinarum Hance Using High-Performance Thin Layer Chromatography-Bioautography. (23rd November 2019) - Zhang, Wan-Xin; Chao, In-Cheng; Hu, De-jun; Shakerian, Farid; Ge, Liya; Liang, Xiao; Wang, Ying; Zhao, Jing; Li, Shao-Ping
Abstract: Background: Alpinia officinarum Hance (ginger family) is an important Chinese medicine, especially in Southern China. Objective: A simple and effective high-performance thin-layer chromatography coupled with 2, 2-diphenyl-1-picrylhydrazyl bioautography (HPTLC-DPPH) and electrospray ionization quadrupole time-of-flight tandem mass spectrometry (ESI-Q-TOF-MS/MS) method was developed for the bioactivity-based quality control of A. officinarum. Methods: The HPTLC-DPPH and ESI-Q-TOF-MS/MS were applied for the analysis of different parts of A. officinarum after using methanol extraction for 23 batches of taproot, four batches of aerial, and three batches of fibril parts. Results: The systematic evaluation showed that similar components in taproot and aerial parts make the major antioxidant activity. However, based on our evaluation, the antioxidant ability of the aerial parts is lower than the taproot parts. There is also a significant difference ( P < 0.05) between taproot and fibril parts of the root. The chemical structures of compounds with the antioxidant capacity were tentatively identified as 5R-hydroxy-7-(4-hydroxy-3-methoxyphenyl)-1-phenyl-3-heptanone (band 1), kaempferide (band 2), and galangin (band 3) based on ESI-Q-TOF-MS/MS analytical results and further confirmed by standards. Conclusions: This identification indicated that two flavonoid compounds and one diarylheptanoid compound possessed high potentials to be used as the antioxidant biomarkers for the quality control of A. officinarum. Highlights: The comparison of different parts could be considered as guidelines for the usage of A. officinarum .